Is Distance to the Nearest Registered Public Automated Defibrillator Associated with the Probability of Bystander Shock for Victims of Out-of-Hospital Cardiac Arrest?. Issue 2 (13th February 2018) - Neves Briard, Joel; de Montigny, Luc; Ross, Dave; de Champlain, François; Segal, Eli
Abstract: Introduction: Rapid access to defibrillation is a key element in the management of out-of-hospital cardiac arrests (OHCAs). Public automated external defibrillators (PAEDs) are becoming increasingly available, but little information exists regarding the relation between the proximity to the arrest and their usage in urban areas. Methods: This study is a retrospective, observational, cross-sectional analysis of non-traumatic OHCA during a 24-month period in the greater Montreal area (Quebec, Canada). Using logistic regression, bystander shock odds are described with regards to distance from the OHCA scene to the nearest PAED, adjusted for prehospital care arrival delay and time of day, and stratifying for type of location. Results: Out of a total of 2, 443 OHCA victims identified, 77 (3%) received bystander PAED shock, 622 (26%) occurred out-of-home, and 743 (30%) occurred during business hours. When controlling for time (business hours versus other hours) and minimum response delay for prehospital care arrival, a marginal negative association was found between bystander shock and distance to the nearest PAED in logged meters (aOR=0.80; CI, 0.64-0.99) for out-of-home cardiac arrests. No significant association was found between distance and bystander shock for at-home arrests. Out-of-home victims had significantly higher odds of receiving bystander shock up to 175 meters of distance to a PAED inclusively (aOR=2.52; CI, 1.07-5.89). Conclusion: For out-of-home cardiac arrests, proximity to a PAED was associated with bystander shock in the greater Montreal area. Strategies aiming to increase accessibility and use of these life-saving devices could further expand this advantage by assisting bystanders in rapidly locating nearby PAEDs. J Neves Briard, L de Montigny, D Ross, F de Champlain, E Segal .Is distance to the nearest registered public automated defibrillator associated with the probability of bystander shock for victims of out-of-hospital cardiac arrest? Prehosp Disaster Med .2018 ;33 (2 ):153 –159 .